2007
DOI: 10.1186/1477-7819-5-19
|View full text |Cite
|
Sign up to set email alerts
|

Multiple rectal carcinoids with diffuse ganglioneuromatosis

Abstract: Although the optimal treatment for the multiple rectal carcinoids remains to be clearly established, it is believed that not all patients with multiple rectal carcinoids (measuring less than 1 cm in diameter) need to have a radical operation. However, the treatment plan for each case should be individualized and a careful follow-up is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…In the Japanese population, rectal NET is the most frequently reported GI tract NET (1). To date, only a few reports of multiple rectal NETs associated with multiple ECMs have been published (2,3,5,6). ECMs may be regarded as the initial phase or intermediate stage of development of a carcinoid tumor (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Japanese population, rectal NET is the most frequently reported GI tract NET (1). To date, only a few reports of multiple rectal NETs associated with multiple ECMs have been published (2,3,5,6). ECMs may be regarded as the initial phase or intermediate stage of development of a carcinoid tumor (3).…”
Section: Discussionmentioning
confidence: 99%
“…In the stomach, such micronests are known as endocrine cell micronests (ECM). However, only a few reports of ECMs have been reported in the colorectum (2,3,5,6), and their significance has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…The growth index, Ki67, of the ganglion cells and nerve fibers was <2%, and no mitotic figures or nuclear pleomorphism were observed, which suggested that DG exhibits an indolent or benign biological behavior. Malignant transformation of DG itself has not been reported, to the best of our knowledge; however, there are a number of case reports of DG coincident with adenocarcinoma (1114), carcinoid tumor (15) or malignant peripheral nerve sheath tumor (1,16). Kanter et al (17) suggested that DG should be considered as a premalignant condition, but this association is controversial (13,18).…”
Section: Discussionmentioning
confidence: 95%
“…As the utility of screening colonoscopy has been increasing, more asymptomatic rectal NETs have been discovered, with most appearing as a single small lesion . The incidence of multiple NETs has been reported to range from 2% to 4.5%; however, multiple rectal NETs with numerous micronests are extremely rare . Treatment options for rectal NET depend on the size of the tumor, the depth of invasion, and the presence or absence of metastasis .…”
Section: Previous Reports Of Multiple Small Rectal Neuroendocrine Tumentioning
confidence: 99%
“…[1][2][3] The incidence of multiple NETs has been reported to range from 2% to 4.5%; however, multiple rectal NETs with numerous micronests are extremely rare. [4][5][6][7][8][9] Treatment options for rectal NET depend on the size of the tumor, the depth of invasion, and the presence or absence of metastasis. 5,10,11 Multicentricity of NET in the small intestine leads to a poor prognosis, but its effects on the prognosis of rectal NET are not fully understood.…”
mentioning
confidence: 99%